(untitled) (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2020)
This research study the properties of two different crude oils . Two samples of crude oil were used, which were ( Al – Dora and Al - Ahdab )crude oil. Atmospheric distillation used to separate these two crude oils into their fractions according to boiling point. This research introduced most important characteristics and information's about these samples of crude oils and their products. ASTM distillation was converted to TPB distillation curve. It was found that the preliminary boiling point is lower than the cease point is higher than ASTM distillation for the two crude oils. Most important properties of the products of the two crude oils were calculated. These properties are API, gravity, Watson characterization factor (k), viscosity, molecular weight and refractive index. It was found that the API gravity for Al-Dora crude oil cuts is less than that of the Al-Ahdab crude oil cuts. Also , Al-Dora and Al-Ahdab crude oils cuts having more naphthenic or aromatic components since the characterization factor is less than 12.5. it was concluded that the characterization factor (K) for Al-Ahdab crude oil is less than Al-Dora crude oil for gasoline only. While the opposite happens with Kerosene and gas oil. Finally , It was conclude that the viscosity, molecular weight and refractive index of Al-Dora crude oil products were higher than that of the products of Al-Ahdab crude oil. It was found also that the viscosity of cuts for Al-Dora and Al- Ahdab crude is increase because kerosene is more viscous (heavy cut) than gasoline. Also gas oil is more viscous than gasoline and kerosene. Finally , it was concluded that the viscosity of gasoline, kerosene and gas oil for Al-Dora crude is higher than gasoline, kerosene and gas oil for Al-Ahdab crude oil. It was concluded that the molecular weights of gasoline, kerosene for Al-Dora crude is higher than gasoline, kerosene for Al-Ahdab crude oil but the gas oil is on the contrary. It was concluded that the refractive index for Al-Dora crude is higher than Al-Ahdab crude oil